Pain-related behaviors and abnormal cutaneous innervation in a murine model of classical Ehlers–Danlos syndrome. Issue 10 (October 2020) - Syx, Delfien; Miller, Rachel E.; Obeidat, Alia M.; Tran, Phuong B.; Vroman, Robin; Malfait, Zoë; Miller, Richard J.; Malfait, Fransiska; Malfait, Anne-Marie
Abstract : Abstract: Classical Ehlers–Danlos syndrome (cEDS) is a connective tissue disorder caused by heterozygous mutations in one of the type V collagen-encoding genes, COL5A1 or COL5A2 . cEDS is characterized by generalized joint hypermobility and instability, hyperextensible, fragile skin, and delayed wound healing. Chronic pain is a major problem in cEDS patients, but the underlying mechanisms are largely unknown, and studies in animal models are lacking. Therefore, we assessed pain-related behaviors in haploinsufficient Col5a1 +/− mice, which clinically mimic human cEDS. Compared to wild-type (WT) littermates, 15 to 20-week-old Col5a1 +/− mice of both sexes showed significant hypersensitivity to mechanical stimuli in the hind paws and the abdominal area, but responses to thermal stimuli were unaltered. Spontaneous behaviors, including distance travelled and rearing, were grossly normal in male Col5a1 +/− mice, whereas female Col5a1 +/− mice showed altered climbing behavior. Finally, male and female Col5a1 +/− mice vocalized more than WT littermates when scruffed. Decreased grip strength was also noted. In view of the observed pain phenotype, Col5a1 +/− mice were crossed with NaV 1.8-tdTomato reporter mice, enabling visualization of nociceptors in the glabrous skin of the footpad. We observed a significant decrease in intraepidermal nerve fiber density, with fewer nerves crossing the epidermis, and a decreased total nerve length of Col5a1 +/− mice compared to WT. In summary, male and female Col5a1 +/− mice show hypersensitivity to mechanical stimuli, indicative of generalized sensitization of the nervous system, in conjunction with an aberrant organization of cutaneous nociceptors. Therefore, Col5a1 +/− mice will provide a useful tool to study mechanisms of pain associated with cEDS. Abstract : Supplemental Digital Content is Available in the Text. Col5a1 +/− mice provide a model of classical Ehlers–Danlos syndrome, a painful heritable disease. Col5a1 +/− mice show hypersensitivity to mechanical stimuli and abnormal cutaneous nociceptive innervation.